The changing structure of UK production, trade and employment: an analysis using input output tables 1974-84 - Greenhalgh, C; Gregory, M; Ray, A (1989)
This paper uses the input output tables for 1974, 1979 and 1984 to explore the causes of changes in employment at sectoral and industry level. We assess the relative importance of rising import penetration, changing producer demands for factor inputs, and changing consumer demands for goods and services as explanations for the contraction of total private sector employment and the rising share of employment in services. The use of input output data and methodology permits us to explore both the direct and indirect consequences of changes in final demand. Whilst the UK has obviously lost markets (and comparative advantage) in labour intensive manufactures, there is not very strong evidence of producers initiating these changes via intermediate demands, reflecting a new international division of labour. Import penetration appears to have been most damaging in final product markets reflecting consumer preferences; by contrast greater sourcing abroad of intermediate products led to loss of employment income in only a limited number of industries. Evidence was found of growing domestic contracting out from manufacturing, particularly in the 1970's, which benefited services. Strong interindustry demand also sustained several growing manufacturing sectors. There was little evidence that growth in consumer spending was biased towards services and away from manufactured goods, although clearly the service component of all goods was rising. The key policy issue thus remains that of retaining markets for final goods.